First record of the non-indigenous fangtooth moray Enchelycore anatina from Rhodes Island, south- eastern Aegean Sea - KALOGIROU, S. (Mediterranean Marine Science, 2010)
The collection of one specimen of the non-indigenous fangtooth moray Enchelycore anatina of tropical Atlantic origin was for the first time found in an area of south eastern Aegean Sea. This record may indicate a recent establishment of the species on the coasts of Rhodes Island and a possible expansion of it on the coastal rocky habitats.